Mouth rinse but not ingestion of a carbohydrate solution improves 1-h cycle time trial performance - Pottier, A.; Bouckaert, J.; Gilis, W.; Roels, T.; Derave, W. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The aim of the present study was to further explore the influence of ingestion and mouth rinse with a carbohydrate-electrolyte solution (CES) on the performance during a ~1 h high-intensity time trial on trained subjects. Subjects rinsed around the mouth or ingested a 6% isotonic CES or placebo (14 mL/kg body weight) before and throughout a time trial in which they had to accomplish a set amount of work (975±85 kJ) as quickly as possible. In the mouth rinse conditions, time to complete the test was shorter (P=0.02) with CES (61.7±5.1 min) than with placebo (64.1±6.5 min), whereas in the ingestion conditions, there was no difference between placebo (62.5±6.9 min) and CES (63.2±6.9 min). Although power output and lactate concentration during exercise were significantly higher when subjects rinsed their mouth with CES compared with placebo, the rating of perceived exertion values did not differ. Blood glucose concentration increased after ingestion of but not after mouth rinse with CES. The interesting finding of the present study is that rinsing the mouth with but not ingestion of CES resulted in improved performance.